Pests, diseases and natural food for Abalone (Haliotis squamata) larvae - Merdekabasuki, Aisyyah Maga; Insani, Liga; Dadiono, Muh Sulaiman (Universitas Tidar, 2024)
The development of seawater cultivation (marineculture) leads to important economic commodities, one of which is shellfish such as abalone shells (Haliotis squamata). Abalone is very popular among people both domestically and abroad, this has caused the demand for abalone to increase. However, most of the abalones are obtained from wild catches. This is what causes the abalone population in nature to decline. Therefore, abalone cultivation, especially seeding, is one way to meet market demand. Problems arise when the larvaes are in the larvae phase, which is susceptible to pest attacks and disease and feed that is appropriate to the size of the abalone larvaes. This research is descriptive research where the primary data collection method is carried out in 3 ways, namely observation, active participation and interviews. This activity aims to find out pests and diseases that attack abalone larvaes and the type of feed that suits the size of the abalone larvaes.